Identification of coverage of quality assurance program for maintenance naval base to the Brazilian conventional nuclear-powered submarine - Eduardo Henrique Damasceno da Gama; Ricardo Kropf Santos Fermam (Brazilian Journal of Radiation Sciences)
The purpose of this study is to identify the coverage of quality assurance program (QAP) to be applied on a Maintenance Naval Base to the Brazilian conventional nuclear-powered submarine. Based on literature review and documents collected at the Angra I nuclear power plant, located in Brazil, it was possible to determine the coverage of QAP for a Brazilian Naval Base that will perform maintenance services on a conventional nuclear-powered submarine. The data were complemented by 6 interviews with specialists from nuclear sector. Regarding the countries that have nuclear-powered submarines, QAP implemented in their Maintenance Bases are confidential information. Another finding, based on the field research, showed that the QAP existing at the Angra I surpassed the 13 requirements established by Standard CNEN-NN-1.16 (Quality Assurance for the Safety of NPP) and, according to the interviewees, can be adapted for the Naval Maintenance Base of the Brazilian Navy. Thus, this study points out 25 requirements that can be used for the establishment of a QAP for the Naval Base in the operation phase of the conventional nuclear-powered submarine; The lack of technical standards and academic literature on the development of QAP, this study can serve as a guideline for the development of a QAP for Maintenance Naval Bases of Nuclear Submarines by the countries interested in this military technology.